Thermomechanical treatment of reinforcing steel - Goryany V.; Radsinsky V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The work deals with application of interstand and after deformation cooling of coiled ( .10, 12 mm) and reinforcing ( .14,16 mm) bar steel in the accelerated cooling installations behind the prefinishing and finishing stands of the light-section mill which provides the formation of the even fine-grained ferrite-perlite structure and reduces grain growth in the mid section of the coil. The application of the roll stock interstand cooling behind the 11th stand together with the afterdeformation accelerated roll stock cooling to 800-8500C enabled us getting reinforcing bar steel diameter .14mm with high impact strength..